Bioinspired Networks of Communicating Synthetic Protocells - Grimes, Patrick J.; Galanti, Agostino; Gobbo, Pierangelo (Frontiers in Molecular Biosciences, 2021)
The bottom-up synthesis of cell-like entities or protocells from inanimate molecules and materials is one of the grand challenges of our time. In the past decade, researchers in the emerging field of bottom-up synthetic biology have developed different protocell models and engineered them to mimic one or more abilities of biological cells, such as information transcription and translation, adhesion, and enzyme-mediated metabolism. Whilst thus far efforts have focused on increasing the biochemical complexity of individual protocells, an emerging challenge in bottom-up synthetic biology is the development of networks of communicating synthetic protocells. The possibility of engineering multi-protocellular systems capable of sending and receiving chemical signals to trigger individual or collective programmed cell-like behaviours or for communicating with living cells and tissues would lead to major scientific breakthroughs with important applications in biotechnology, tissue engineering and regenerative medicine. This mini-review will discuss this new, emerging area of bottom-up synthetic biology and will introduce three types of bioinspired networks of communicating synthetic protocells that have recently emerged.